The audit committee as moderating the effect of hexagon's fraud on fraudulent financial statements in mining companies listed on the Indonesia stock exchange - Maylia Pramono Sari; Era Mahardika; Dhini Suryandari; Surya Raharja (Cogent Business & Management, 2022)
The six components of the hexagonal fraud theory are represented in this study by external pressure variables, change in auditors, the nature of the industry, the CEO's dual role, change in directors, and political connections. Additionally, a statistical analysis is done to determine whether the audit committee can moderate the impact of independent variables on dependent variables. The study's population consisted of 73 mining-related firms that were listed on the Indonesia Stock Exchange between 2018 and 2020. Purposive sampling is used in the sample selection method to get 173 units of analysis. Utilizing documentation procedures, data is gathered. Panel data regression is used in this study analysis tool. The findings demonstrated that the change in directors' factors has a negative and substantial impact on the detection of fraudulent financial statements, whereas the nature of industry variables has a positive and significant impact. However, there is no discernible difference between the variables of external pressure, change in auditors, CEO dualism, and political connection when it comes to identifying fraudulent financial statements. The findings of this study also demonstrate that the audit committee can reduce the impact of the industry's cyclical structure and shift of directors on the detection of fraudulent financial statements. The audit committee was unable to control the impact of outside pressure, change in auditors, the CEO's dual role, and political ties on fraudulent financial statements, though. This research provides theoretical and practical implications for internal and external companies, especially investors and the government in detecting fraudulent financial statements.
Keywords: 650; audit committee; fraud hexagon theory; Fraudulent financial statement